Structural, morphological, and optoelectrical characterization of Bi2S3 thin films grown by co-evaporation (2016)
This work presents the results of synthesis and characterization of polycrystalline n-type Bi2S3 thin films. The films were grown through a chemical reaction from co-evaporation of their precursor elements in a soda-lime glass substrate. The effect of the experimental conditions on the optical, morphological structural properties, the growth rate, and the electrical conductivity (?) was studied through spectral transmittance, X-ray diffraction (XRD), atomic force microscopy (AFM) and ? versus T measurements, respectively. The results showed that the films grow only in the orthorhombic Bi2S3 bismuthinite phase. It was also found that the Bi2S3 films present an energy band gap (Eg) of about 1.38 eV. In addition to these results, the electrical conductivity of the Bi2S3 films was affected by both the transport of free carriers in extended states of the conduction band and for variable range hopping transport mechanisms, each one predominating in a different temperature range. © 2016 World Scientific Publishing Company.